If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+1/7(X)+1/11(X+1/7(X))=60
We move all terms to the left:
X+1/7(X)+1/11(X+1/7(X))-(60)=0
We can not solve this equation
| 15m+(–5m)=10m | | 15.5q+17.66=14.4q+4.68 | | 12=2+7x-4 | | 18q=19q+16 | | -3(2x+7)=4x+19 | | 5a+8=3a+2 | | -2(4n-2)-2n=54 | | 8x^2-9=-43 | | 6(-6x+4)=168 | | (7x-5)=(x+1)(x+1) | | 70=10x-1/4x | | -3(x-2)/6=2(x-1) | | -3/3n=8 | | 2n+(-6)+12=-4 | | -19-12s=19-10s | | -3x+25=-15+2x | | 4z+3/4=5z=5/4 | | 2(m+7)=3(m+2) | | x+2(x+10)=83 | | 4x+-7=-10x8 | | 0.75=0.4x+0.5 | | -15+k=-9 | | Y=0.1-0.005xX=6 | | -2(y+3)+4=14 | | 9x+1-5x=8+3x+2 | | -10-3u=-2u+8 | | 6x-7+3x=4+5+x | | d(4)=40(4) | | x=(5x-12) | | −6(x−1)=108 | | 12+5f+17f=-9+19f | | –2s=–s+7 |